Critical discourses of old age and telecare technologies - Akdur, Gizdem (New York : Routledge, 2020)
"This book makes an enquiry into policies surrounding old age and telecare. It contextualises telecare within the wider history of health and social care in England to build the case that there are grand narratives of old age embedded in policies"--
List of figuresList of TablesAcknowledgements1. Introduction: Connecting Old Age with Telecare 2. A General Review of Old Age and Telecare 3. A Critical Enquiry into Discourses and Identity of Old Age 4. Conclusions and Future DirectionsReferencesAppendicesIndex
OCLC-licensed vendor bibliographic record.
Keywords: Older people -- Services for; Telecommunication in medicine; SOCIAL SCIENCE / Human Services; MEDICAL / Geriatrics; SOCIAL SCIENCE / Gerontology